(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
While big data applications in cloud computing are rapidly growing in popularity, privacy issues have increased dramatically. Encrypting data in real time is one of the most important issues during data processing and transfer. In order to reach an acceptable performance level, many modern applications forego data encryptions, which is incompatible with privacy concerns. This article covers several virtualized processes and analyses the cloud technology safety challenge and way to solve in brightness of cloud technology ideas and characteristics. Information confidentiality and dependability of services are major cybersecurity problems in internet applications. A singular monitoring platform will not address the cloud hosting privacy challenge; to defend the whole clouds infrastructure, a mix of old and new methods and technology must be employed in harmony. The author demonstrates the use of encoding and decoding techniques in aspects of the data confidentiality, computation time, and virtualized systems effectiveness. On top of this infrastructure, they may enable dynamically data storage functions on encoded information sections for inclusion, deleting, and updating, which we think will be future work for improvement.